How are police doing in combating crime? An exploratory study of efficiency analysis of the Policía Nacional Civil in Guatemala. Issue 1 (11th March 2014) - Alda, Erik
Abstract : Purpose: – In almost all modern societies, police forces are at the forefront of ongoing activities to reduce and prevent crime. Both in practice and in popular belief, police forces are the visible presence for maintaining security and safety to citizens in municipalities, towns and cities, and from cities to local neighborhoods. This paper aims to investigate how efficiently the police in Guatemala are in combating crime using data envelopment analysis (DEA). Design/methodology/approach: – The study used DEA to measure the efficiency of police stations in fighting crime in Guatemala based on their inputs and outputs. Findings: – The analyses showed that only four out of 22 police departments were considered efficient. The average efficiency score for the 22 police departments was 62 percent. Research limitations/implications: – Data on crime and police are limited in Guatemala. Further research using DEA would be particularly relevant if the methodology included: a wider range of inputs/outputs, longer panel data, and more precise estimates of the effect of contextual variables. The findings of the study can inform police managers and policymakers to allocate security resources more efficiently. Practical implications: – Given the low levels of inefficiency of police departments in Guatemala, police management would have to ensure that clearance rates increase significantly by either increasing the human resource capacity of the police departments according to the needs so that clearance rates can be improved and be more effective and efficient in combating crime. Originality/value: – This is the first in depth study of police efficiency in Central America. In an increasingly resource strapped environment employing DEA might be a useful tool to improve human and financial resource allocation.